STUDI ETNOBOTANI PADA RAGAM KULINER KHAS SUMATRA BARAT DI KABUPATEN PADANG PARIAMAN - Khumaira, Kayla Anaya; Kardiman, Reki; Ade, Filza Yulina; Chatri, Moralita; Sujarwo, Wawan (Universitas Jambi, 2025)
The importance of preserving traditional cuisine based on the utilization of local plants as mainingredients, spices, and herbs represents a key effort in safeguarding cultural heritage.Padang Pariaman Regency was selected for this study due to its richMinangkabau culinarytraditions supported by natural resources and local wisdom. This study aimed to identifyMinangkabau traditional dishes made from local plants in Padang Pariaman Regency, WestSumatra, as part of cultural preservation efforts. The Participatory Ethnobotanical Appraisal(PEA) method was applied through in-depth interviews with 30 respondents across fivevillages. The results showed 34 types of traditional dishes utilizing 49 plant species from 24families, mainly the fruits, leaves, andseeds, commonly processed by grinding, with theprimary source of ingredients being local markets. This study emphasizes the importance ofdocumenting local knowledge to safeguard the Minangkabau culinary heritage. The findingsalso highlight the significant potential of local biodiversity for further development, both inpreserving traditional community knowledge and as a foundation for the development ofculinary products based on local spices. Therefore, collaborative support is needed to promotethe conservation of local plant resources and the innovation of economically valuable productsrooted in local wisdom.